Rachel Gray: A Tale Founded on Fact - Kavanagh, Julia, 1824-1877 (Salt Lake City, UT : Project Gutenberg, 2011)
"Rachel Gray: A Tale Founded on Fact" by Julia Kavanagh is a novel written in the mid-19th century. The story centers around the life of Rachel Gray, a dressmaker lost in quiet contemplation, navigating her modest and often challenging existence in a neglected section of London while grappling with her feelings of loneliness and longing for connection, particularly with her estranged father. The narrative weaves through her encounters with others in her life, including her apprentices and local residents, revealing the stark contrasts between her hopes and everyday realities. At the start of the book, the setting is established as a decaying street on the outskirts of London, with an atmosphere that reflects Rachel's internal struggles. The opening chapters introduce Rachel as a woman in her late twenties, characterized by her quiet intellect and deep sensitivity, working diligently as a dressmaker under the critical eye of her stepmother, Mrs. Gray. The narrative fleshes out her simple yet profound interactions, such as her tender recollections of her deceased sister, moments of beauty in her observations, and her tentative hopes for her father's acknowledgment. The story hints at a deeper connection with her father and explores Rachel's ardent yearning for familial love, setting the stage for her personal journey against the backdrop of societal indifference. (This is an automatically generated summary.)
Release date is 2011-05-18
Keywords: London (England) -- Fiction; Christian life -- Fiction; Poor -- Fiction